2015
DOI: 10.1007/s00248-015-0676-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity in the Soda Saline Crater Lake from Isabel Island, Mexico

Abstract: Isabel Lake is a moderate saline soda crater lake located in Isabel Island in the eastern tropical Pacific coast of Mexico. Lake is mainly formed by rainfall and is strongly affected by evaporation and high input of nutrients derived from excretions of a large bird community inhabiting the island. So far, only the island macrobiota has been studied. The knowledge of the prokaryotic biota inhabiting the upper layers of this meromictic lake can give clues for the maintenance of this ecosystem. We assessed the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
1
14
0
1
Order By: Relevance
“…Moreover, the γ-proteobacteria genera Halomonas and Shewanella were enriched in seven of the nine haze events, and their average relative abundances were significantly and positively correlated with RH. Halomonas mainly are isolated from highly saline environments, such as oceans and salt lakes ( Aguirre-Garrido et al, 2016 ; Li Z. et al, 2016 ), alkaline-saline soils ( Dou et al, 2015 ), and dumps polluted by solid wastes ( Mwaikono et al, 2016 ). These organisms have great tolerance for high concentrations of nitrate and salinity ( Liao et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the γ-proteobacteria genera Halomonas and Shewanella were enriched in seven of the nine haze events, and their average relative abundances were significantly and positively correlated with RH. Halomonas mainly are isolated from highly saline environments, such as oceans and salt lakes ( Aguirre-Garrido et al, 2016 ; Li Z. et al, 2016 ), alkaline-saline soils ( Dou et al, 2015 ), and dumps polluted by solid wastes ( Mwaikono et al, 2016 ). These organisms have great tolerance for high concentrations of nitrate and salinity ( Liao et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al ( 2006 ) demonstrated that when salinity increase, the relative abundance of Betaproteobacteria class members decreases, but the relative abundance of Apha- and Gammaproteobacteria taxa increases. These results agreed with different studies carried out in continental waters (Böckelmanna et al, 2000 ; Brümmer et al, 2000 ), estuaries (del Giorgio and Bouvier, 2002 ; Kirchman et al, 2005 ; Henriques et al, 2006 ; Zhang et al, 2006 ), solar salterns (Benlloch et al, 2002 ), and a DGGE study in the soda saline crater lake from Isabel island, in the eastern tropical Pacific coast of Mexico (Aguirre-Garrido et al, 2016 ). In our study, the sequences affiliated to class Alpha- and Betaproteobacteria showed a negative correlation with salinity and positive with oxygen and pH, whilst class Gammaproteobacteria was positively related to salinity.…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification conditions consisted in 25 cycles using 55 °C as annealing temperature as described by Aguirre-Garrido et al . 50 .…”
Section: Methodsmentioning
confidence: 99%